(untitled) (Progress Annals: Journal of Progressive Research, 2025)
This article analyzes key operational challenges in the pneumatic transportation of raw cotton, including material clogging inside the pipeline, increased aerodynamic resistance, and high energy consumption. A new technological solution is proposed based on applying vibrational excitation to the walls of the pneumatic pipeline using an electrically powered system. The influence of vibrational effects on the coupled air–cotton flow dynamics was modeled, and the effects of vibration amplitude and frequency on pressure losses and suction distance were theoretically substantiated. Research findings demonstrate that the application of vibrational technology increases the cotton suction distance by approximately 1.4–1.6 times while reducing energy consumption by 15–25%, thereby enhancing operational reliability and energy efficiency